ANALISIS KESULITAN PEMBELAJARAN GEOMETRI KELAS 4 SD SERTA PERAN GEOGEBRA DALAM MENANGGULANGI KESULITAN SISWA - Imelda Meyvita; Anisah Nur Azizah; Kowiyah (STKIP Subang, 2024)
This study aims to analyze the challenges faced by fourth-grade students in understanding geometry and to explore how GeoGebra can assist in overcoming these difficulties. Geometry is an essential aspect of mathematics that supports the development of logical and spatial thinking skills. However, many students struggle to grasp basic concepts such as the properties of two-dimensional and three-dimensional shapes, spatial visualization, and the use of symbols and measuring tools. Several factors influencing these challenges include unengaging teaching methods and a lack of learning media. GeoGebra, an interactive software that integrates geometry and algebra, offers an innovative approach through dynamic visualization that can enhance students' understanding. Utilizing a descriptive qualitative method and collecting data through observations and interviews at a public elementary school in East Jakarta during the 2024/2025 academic year, the research findings indicate that GeoGebra can improve students' conceptual understanding of geometry, visualization skills, and the use of measuring tools and geometric symbols. This study also recommends providing training for teachers in using GeoGebra and applying various teaching approaches to enhance the effectiveness of geometry learning, with the hope of improving students' mathematics learning outcomes at the elementary level.